When the Benign Pneumatosis Intestinalis Becomes No Longer Benign: A Rare Case of Bowel Perforation in a Patient with Systemic Sclerosis - Jian Guan; Alvina Munaf; Alric V. Simmonds; Irteza Inayat (Case Reports in Gastrointestinal Medicine)
Systemic sclerosis is a multisystem disease featured with autoimmunity and organ fibrosis. Although gastrointestinal (GI) tract involvement is common in patients with systemic sclerosis, colonic perforation is extremely rare. Benign pneumatosis intestinalis, a phenomenon more frequently seen in rheumatologic conditions, makes the diagnosis of colonic perforation even more challenging. We report a unique case of colonic perforation in a patient with chronic systemic sclerosis. This patient initially presented with mild abdominal pain and hematemesis. Urgent upper endoscopy was unremarkable and radiology showed stable pneumatosis intestinalis. Due to worsening abdominal pain, laparotomy exploration was performed and colonic perforation with transmural ischemic necrosis was found.